Genome sequence and transcriptome analyses of the thermophilic zygomycete fungus Rhizomucor miehei - Zhou, Peng (BioMed Central, 2014)
BACKGROUND: The zygomycete fungi like Rhizomucor miehei have been extensively exploited for the production of various enzymes. As a thermophilic fungus, R. miehei is capable of growing at temperatures that approach the upper limits for all eukaryotes. To date, over hundreds of fungal genomes are publicly available. However, Zygomycetes have been rarely investigated both genetically and genomically. RESULTS: Here, we report the genome of R. miehei CAU432 to explore the thermostable enzymatic repertoire of this fungus. The assembled genome size is 27.6-million-base (Mb) with 10,345 predicted protein-coding genes. Even being thermophilic, the G + C contents of fungal whole genome (43.8%) and coding genes (47.4%) are less than 50%. Phylogenetically, R. miehei is more closerly related to Phycomyces blakesleeanus than to Mucor circinelloides and Rhizopus oryzae. The genome of R. miehei harbors a large number of genes encoding secreted proteases, which is consistent with the characteristics of R. miehei being a rich producer of proteases. The transcriptome profile of R. miehei showed that the genes responsible for degrading starch, glucan, protein and lipid were highly expressed. CONCLUSIONS: The genome information of R. miehei will facilitate future studies to better understand the mechanisms of fungal thermophilic adaptation and the exploring of the potential of R. miehei in industrial-scale production of thermostable enzymes. Based on the existence of a large repertoire of amylolytic, proteolytic and lipolytic genes in the genome, R. miehei has potential in the production of a variety of such enzymes.